Brain Vital Signs Detect Information Processing Differences When Neuromodulation Is Used During Cognitive Skills Training - Smith, Christopher J.; Livingstone, Ashley; Fickling, Shaun D.; Tannouri, Pamela; Campbell, Natasha K.J.; Lakhani, Bimal; Danilov, Yuri; Sackier, Jonathan M.; D’Arcy, Ryan C.N. (Frontiers in Human Neuroscience, 2020)
Background: Neuromodulation through translingual neurostimulation (TLNS) has been shown to initiate long-lasting processes of neuronal reorganization with a variety of outcomes (i.e., neuroplasticity). Non-invasive TLNS is increasingly accessible through the Portable Neuromodulation Stimulator (PoNS®), a medical device that delivers electrical stimulation to the tongue in order to activate the trigeminal (V) and facial (VII) cranial nerves. Anecdotal reports from previous clinical studies have suggested incidental improvements in cognitive function. To objectively explore this observation, we examined TLNS-related effects on the semantic N400 brain vital sign cognitive response during cognitive skills training in healthy individuals. Methods: Thirty-seven healthy volunteers were randomized to receive simultaneous TLNS (treatment) or no TLNS (control) while undergoing cognitive skills training. Cognitive training was conducted for two 20-minute sessions (morning and afternoon/evening) over three consecutive days. Brain vital signs were evaluated at baseline, Day 1, and Day 3. Analyses focused on cognitive processing as measured by N400 changes in amplitude and latency. Results: Over the 3-day course of cognitive training, the N400 amplitude decreased significantly in the control group due to habituation (p=0.028). In contrast, there was no significant change in the TLNS treatment group. Conclusion: TLNS led to a sustained N400 response during cognitive skills training, as measured by the brain vital signs framework. The study findings suggest differential learning effects due to neuromodulation, consistent with increased attention and cognitive vigilance.